PENGARUH KOMITE AUDIT KOMISARIS INDEPENDEN DAN UKURAN KAP TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR PADA BEI TAHUN 2012-2015 - Ganefo Sudirman (Universitas Pamulang, 2018)
Abstract RThe research is an empirical study to examine the influence of audit committee, independent commissioner and public accounting firm size to earnings management on Indonesian Stock Exchange listed companies from manufacturing various industry sector in 2012 until 2015. The sample collected using the purposive sampling method and it has resulting 15 companies for the samples.The sample was analyzed by using linear multiple regression technique. T-test for testing the hypothesis and f-test for the feasibility model with the five percent level of significant. It was tested with classical assumption test like normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. The result shows audit committee has a negative and significant to earning management, independent commissioner committee has insignificant influence to Earnings Management, and KAP size has a positive and significant to earning management Keywords: Audit committee, independent commissioner and public accounting firm size, earnings management